Effect of host plants on development and reproduction of Diaphorina citri and their host preference. Issue 8 (3rd June 2022) - Meng, Lixue; Cheng, Xiaoqin; Xia, Changxiu; Zhang, Hongyu
Abstract: The effects of five host plant species – tangerine, Citrus reticulata Blanco cv. Shatangju, C. reticulata cv. Ponkan, orange jasmine, Murraya paniculata (L.) Jack, lemon, Citrus limon (L.) Osbeck, and navel orange, Citrus sinensis (L.) Osbeck (all Rutaceae) – on the life‐table parameters and host preference of the citrus psyllid, Diaphorina citri Kuwayama (Hemiptera: Liviidae), were evaluated under laboratory conditions. In the presence of the host plants tested, citrus psyllid showed higher preference for navel orange, followed by Shatangju and orange jasmine. Total nymph duration of D. citri was longest on lemon (14.1 days) and shortest on Shatangju (12.7 days). The survival rate (lx ) of citrus psyllid on orange jasmine was significantly higher than on other tested host plants. The highest longevity of females was observed on lemon (47.6 days), whereas the shortest was on navel orange (40.5 days). The total number of eggs laid by females was not significantly different among host species. The net reproductive rate (R0 ) was significantly affected by host plants, being highest on Shatangju (162.1 females/female per generation) and lowest on navel orange (130.7). The intrinsic rates of natural increase (rm ) was not significantly different among hosts, and ranged from 0.112 on lemon to 0.123 on orange jasmine. Cluster analysis of the life‐table parameters of D. citri on five host plant species indicated that Shatangju was the most suitable host to D. citri, followed by orange jasmine, and navel orange was the least suitable. Abstract : Diaphorina citri (Hemiptera: Liviidae) is a phytophagous insect that feeds on the sap of citrus trees and has a narrow host range (Rutaceae species). Host plants were grouped within clusters according to the life‐table parameters of D. citri reared on each of five host plants under laboratory conditions. Cluster A consisted of orange jasmine and Shatangju as the most suitable hosts, subcluster B1 (lemon and Ponkan) was an intermediate group, and subcluster B2 (navel orange) was the least favorable host.